Upaya Memberdayakan Warga Desa Karangpranti untuk Meningkatkan Produktifitas Abon Kluwih Padaumkm Abon Hj. Sun Dalam Rangka Pencegahan Stunting - Wawan Susilo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2019)
Karangpranti Village is a village located in Pajarakan District, Probolinggo Regency. The local advantage of the Karangpranti village is that there are several superior MSMEs that seek to empower the surrounding residents to build and help improve the economy of the surrounding residents. One of the MSMEs that is quite helpful in providing employment in the Karangpranti village is Abon Hj. Sun. However, the development of MSME Abon Hj. Sun is constrained by the lack of capital and public knowledge about the empowerment of its citizens. So that solutions can be done to overcome existing obstacles, for example, Students hold a Micro Small and Medium Enterprises (MSME) Socialization, Expanding production land, Assistance for capital submission. The method used is the preparation stage includes a survey or observation, evaluation of problems and preparation, then the implementation phase which includes approaches to the community and MSME socialization, then the evaluation stage is carried out to see the success rate of activities starting from the beginning, the process, to the achievement of the results of activities . If the productivity of MSME Abon Hj. Sun is increasingly being developed so that efforts to empower residents around Karangpranti village will be increasingly realized, so that the welfare of the people can be increasingly created. So that the increase in welfare can prevent stunting in the Karangpranti village community. Keywords : Productivity, Community Health, Prevention of Stunting